Entre blocos afros e afoxés: Liberdade Salvador/BA no último quartel do séc. XX (identidade e diferença na intersubjetividade) - Mendes, Bartolomeu de Jesus (2008)
With the same investigative effort initiated in the course of Masters, seeking detect cultural characteristics that enable reveal traces of possible identities in the Neighborhood of Liberty - Salvador / BA, from studies on the origins of the individuals who gave social origin, repeats now the problem, as doctoral process, giving continuity and development in reflection, deepen further in their detail, trying to understand the process of identity construction, set in networks of inter-subjectivities made by its people in their everyday social relations, in the interior of the blocks afros and Afoxés's own neighborhood. The presence of diverse cultural elements, distributed in a topographical scenario also setup diverse, makes the neighbourhood under study, reveal tensions and conflicts, making more complicated the formatting of a vision that understands the construction essentialist identity as pure result of belonging to a given location or social group. Moreover, the very social subjects, spread simultaneously in the various instances of social groups, taking their influences and contributions to them, print in identity profiles, cultural nuances, making the groups more open to the polyphony of its members, participating so, as active elements of the whole process of individual construction and collective identities